2018
DOI: 10.1080/17461391.2018.1490459
|View full text |Cite
|
Sign up to set email alerts
|

Differences in step characteristics and linear kinematics between rugby players and sprinters during initial sprint acceleration

Abstract: The initial steps of a sprint are important in team sports, such as rugby, where there is an inherent requirement to maximally accelerate over short distances. Current understanding of sprint acceleration technique is primarily based on data from track and field sprinters, although whether this information is transferable to athletes such as rugby players is unclear, due to differing ecological constraints. Sagittal plane video data were collected (240 Hz) and manually digitised to calculate the kinematics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 41 publications
(68 reference statements)
1
39
0
2
Order By: Relevance
“…While previous studies showed contradiction about the determinants of the initial sprint acceleration performance of field sport athletes in terms of SL and SF [7,8,9], the only study employed soccer players elucidated that the greater running speed was associated with greater SL [7]. The results in this study support the previous finding [7] and indicates the importance of SL for greater increment of running speed during the initial acceleration phase in soccer players.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…While previous studies showed contradiction about the determinants of the initial sprint acceleration performance of field sport athletes in terms of SL and SF [7,8,9], the only study employed soccer players elucidated that the greater running speed was associated with greater SL [7]. The results in this study support the previous finding [7] and indicates the importance of SL for greater increment of running speed during the initial acceleration phase in soccer players.…”
Section: Discussionsupporting
confidence: 77%
“…The results in this study support the previous finding [7] and indicates the importance of SL for greater increment of running speed during the initial acceleration phase in soccer players. Although the running speed was associated with SF in previous studies using field sport athletes [8,9], magnitude of SF was relatively high in the current study compared to those in the previous studies (4.65 ± 0.24 Hz in the 1st–4th step section in this study versus 3.64 and 3.34 Hz in the initial three steps in the study by Murphy et al [8] and ranged from 4.0 to 4.6 Hz during the initial three steps in the study by Wild et al [9]). These indicate that baseline of SF was high during the initial acceleration phase in this study, and this high SF would limit the variation of SF possibly mitigating the association of SF with increment of running speed.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The word "elite" is overused in sports science literature, and the number of published studies on the biomechanics of the world's best able-bodied sprinters is small. Out-of-competition data have been presented from the block start (Bezodis et al, 2015;Willwacher et al, 2016), initial acceleration phase (Wild et al, 2018), composite 40 m maximal acceleration (Rabita et al, 2015), maximum velocity phase (Bezodis et al, 2008(Bezodis et al, , 2018, and a full 100 m sprint (Morin et al, 2012) of groups of athletes that generally contained one sub-10 s sprinter. There are also examples of analyses of elite 100 m races based primarily on distance-time data, either taken from broadcast television footage or data from previous IAAF biomechanics projects (e.g., Salo et al, 2011;Taylor and Beneke, 2012;Slawinski et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…MBI provides categories of evidence, such as "possible", "likely", and "very likely" beneficial. We found that researchers employed MBI's evidence thresholds much like significance thresholds: They highlighted results that met the bars of "possible", "likely", or higher in tables and figures with symbols to distinguish the achieved thresholds much like the use of symbols for p<0.05 or p<0.01; for examples, see: [30][31][32]. They then made claims about effects based on meeting a minimum MBI evidence threshold, usually either "possible" or "likely."…”
Section: Plos Onementioning
confidence: 99%